Analysis of polyadenylation site usage of the c-myc oncogene. - Laird-Offringa, I A (1989)
The c-myc gene contains 2 well conserved polyadenylation (pA) sites. In all human and rat cell lines from various differentiation stages and tissue types the amount of mRNA terminating at the second pA site is 6-fold higher than the amount ending at the upstream site. This is not due to a difference in stability of the two mRNA types and therefore must be due to preferential usage of the downstream site. The usage of the pA sites is not altered during growth factor induction of quiescent cells. We have not been able to detect differences in behavior between mRNAs ending at either pA site. Both types of mRNA are induced upon treatment of cells with cycloheximide. Furthermore, we have shown that the poly(A) tail of c-myc mRNA is lost during degradation of the messenger, as was described previously for c-myc mRNA in an in vitro system. The time required for the loss of the poly(A) tail is similar to the half-life of c-myc mRNA.